The Effect of pH and Anion Adsorption on Formic Acid Oxidation on Au(111) Electrodes. (20th July 2021) - Hermann, Johannes M.; Abdelrahman, Areeg; Jacob, Timo; Kibler, Ludwig A.
Abstract: The impact of solution pH has been investigated for the electrooxidation of formic acid on Au(111), taking the mole fraction of formate in solution as the relevant parameter. The electrocatalytic current density is increasing with rising pH and reaches a plateau for pH > 4. The pH-dependence of characteristic potentials shows systematic trends for the onset of the reaction, the peak maximum, and the phase transition within the formate adlayer. After the addition of phosphate buffer, a substantial deactivation by specific adsorption of phosphates and a bell-shaped curve for the maximum current density as a function of pH is found. The general behavior of co-adsorbing anions is addressed at low pH using various oxyanions to get more insight into the role of adsorbed formate. While non-carboxylate anions are displaced by formate at high potentials, mixed phases are observed for formate and other carboxylates. Graphical abstract: Image, graphical abstract